INTERSEXUAL DIFFERENCES IN BODY TRAITS IN SELECTED COCKROACH SPECIES - Górecki, Marcin; Kaźmierczak, Sandra; Pojasek, Aleksander (Polish Journal of Natural Sciences, 2023)
In cockroaches sexual dimorphism in body size is common and all patterns are exhibited, however female size bias predominates. The aim of present study was to evaluate intersexual differences in body dimension and weight in 12 cockroach species: Blaberus craniifer, Blaberus discoidalis, Blaberus boliviensis, Eublaberus posticus, Eublaberus distanti, Archimandrita tessellata, Blaptica dubia, Panchlora nivea, Nauphoeta cinerea, Phoetalia pallida, Shelfordella lateralis and Periplaneta americana. Fifty males and fifty females imagines of each species were weighted and their body length, length and width of pronotum and length of antennae were measured. In all species female-biased sexual size dimorphism was shown: female were significantly heavier and their pronota were longer and wider. Also females body length obtained higher values in 10 out 12 species. In other two species intersexual differences in body length appeared to be insignificant. On the other hand, males antennae were significantly longer in majority of studied species, with exception of P. nivea, P. pallida and N. cinerea. Thus, in majority of studied species although males were smaller, they had longer antennae. Female-biased sexual size dimorphism is common in invertebrates and possession of longer antennae by males can be explained by their need of detecting female pheromones.